English Language Teaching Materials and Religious Moderation in Indonesian Primary Schools: A Narrative Case Study - Ghufron, M. Ali; Rohman, Taufiqur; Aditia, M. Rifki (Lingua Cultura, 2024)
The research observed the gap in understanding how English Language Teaching (ELT) materials in Indonesian primary schools promoted religious moderation and fostered values such as tolerance and respect for diversity. Utilizing a narrative case study approach, it examined the role of ELT materials in advancing religious moderation. Through an analysis of ELT textbooks and supplementary resources, the research evaluated the representation of religious moderation themes and explored teachers’ perceptions and use of these materials in their classrooms. The research contributed to the broader discourse on education’s role in fostering peace and tolerance, providing insights for policymakers, educators, and curriculum developers. Applying a qualitative narrative case study design, the research captured the experiences of English language teachers from three primary schools in diverse settings in Pekalongan, Central Java, Indonesia. Data were collected through in-depth interviews, document analysis, and classroom observations, with validation techniques such as triangulation and member checking ensuring credibility. Thematic analysis was used to systematically analyze the data. Findings reveal both the potential and limitations of ELT materials in promoting religious moderation. While textbooks feature characters from diverse cultural and religious backgrounds, they often lack explicit integration of religious moderation values, focusing more on language skills. Teachers address these gaps with supplementary strategies, including additional stories, activities, and discussions that emphasize religious diversity and interfaith tolerance. The research highlights the need for curriculum developers to prioritize religious moderation in educational materials and for policymakers to support professional development initiatives for teachers. Implementing these recommendations can better equip students with values essential for fostering a harmonious and inclusive society.